Frequency stability analysis of virtual power plants in a microgrid using load droop control method - Sukit Ingprasert; Singh, Jai Govind; Weerakorn Ongsakul; Kuwornu, John K. M.; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2018)
Wind and solar energy sources are cost-effective to sustenance the generation part of energy in the future energy demand. Moreover, renewable energy sources (RESs) will substitute for the traditional generation. RESs have the inherent fluctuation and intermittence of power output of these sources. The type of WTs is considered the doubly-fed induction generator (DFIG). Therefore, this uncertainty of these generators may exacerbate the stability and protection of power system. Energy storage systems and dump loads were significant to disentangle this problem. However, they are very expensive for this fluctuation. Therefore, the coordination control between RESs and controllable load in virtual power plant (VPP) is proposed in this study. The control method of power consumption in controllable load is also proposed for providing the power output of the VPP. Moreover, the coordination between the power output of RESs and the droop load power consumption of controllable loads can provide the flexibly power output of the VPP. Furthermore, the frequency droop control of controllable loads will response the frequency deviation. When the system frequency is over frequency in power system, the controllable loads will increase their power consumption in the VPP for the frequency regulation. Moreover, the frequency droop control of the power consumption of these loads will decrease their power consumption when the system frequency dropped. WTs have the over power reduction to control the power output of WTs when grid frequency increased. Therefore, VPP is externally adjustable and fulfill important functions electrically connected with the use of energy resources, such as distributed control frequency. The island microgrid and IEEE 33 bus system are the test system of this work. This simulation study the load variation in this system. VPP will included the WTs and PVs for the island microgrid. Moreover, IEEE 33 bus system is included the DFIG and diesel generators. For this system, This work use the DIgSILENT software for studying the system frequency variation by the coordination between the control of WTs and the frequency droop control of the controllable loads in the virtual powerplant. Simulation results provide 3 cases of island microgrid: 2 WTs are installed in the VPP, PV and WT included in the VPP and PVs installed in VPP. Moreover, the controllable load provide the two group of loads to response the frequency deviation. Simulation results confirm the effectiveness of the VPP in providing support to the microgrid frequency of the island microgrid and IEEE 33 bus system.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Energy
Thesis (M.Eng.) - Asian Institute of Technology, 2018
Keywords: Electric power-plants -- Decision making; Microgrids (Smart power grids); Renewable energy sources -- Analysis